Pseudomentalization as a Challenge for Therapists of Group Psychotherapy With Drug Addicted Patients - Esposito, Giovanna; Formentin, Silvia; Marogna, Cristina; Sava, Vito; Passeggia, Raffaella; Karterud, Sigmund W. (Frontiers in Psychology, 2022)
One of the main challenges in group therapy with drug addicted patients is collective pseudomentalization, i.e. a group discourse consisting of words and clichés that are decoupled from any inner emotional life and are poorly related to external reality. In this study we aimed to explore the phenomenology of pseudomentalization and how it was addressed by the therapist in an outpatient group for drug addicted patients. The group was composed of seven members and the transcripts of eight audio-recorded sessions (one per month) were rated and studied. The therapist’s interventions were measured with the mentalization-based group therapy adherence and quality scale by independent raters. Two sessions, one with the highest and one with the lowest adherence, were selected, and the clinical sequences of pseudomentalization were analysed in a comparative way. The findings revealed that pseudomentalization does occur as a collective phenomenon, akin to Wilfred Bion’s “basic assumptions” which we reconceptualize in this study. Any pseudomentalization seemed to be reinforced by the therapist when she was presenting frequent and long interventions, when abstaining from the management of group boundaries, when providing questions focused more on content than on the mental states of the group members and when not focusing on emotions. However, the ultimate source of collective pseudomentalization seemed to be the group members’ fear of being overwhelmed by painful emotions, mental confusion and a loss of identity. The findings also indicated that the principles of mentalization-based group therapy may be a good antidote to pseudomentalization.